(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa metodologica - 2. Cenni storici sulle comunità musulmane francesi - 3. La re-invenzione di una tradizione? - 4. Mangiare halal a scuola: l’affaire di Chalon-sur-Saône - 5. Conclusioni. Halal alimentation and the challenges against french laïcité: the request of alternative menu in the school canteens ABSTRACT: The article will concern the debate about the balance between secularism and religious-driven prerogatives through a narrow focus on the diffusion of halal food in France. In particular, I will shed light on the increasing request of shari’a-compliant food by Muslims in some social spaces, for instance in the school canteens. My research will unfold its arguments in two sections. In the first one, I will address the recent development of halal market in France and try to frame the reasons of such burgeoning activities - revival of Islam or neoliberal marketing strategy? In the second part, I will consider the sentence of Dijon Administrative Tribunal, which in 2017 abolished the decision of the mayor of Chalon-sur-Saône of suppressing halal menu in the school canteens. The verdict might be read as an opinion favourable to Muslim’s prerogatives. Nonetheless, the rationale of the judgement does lie indeed in the defence of the “best interest of the child”, whereas the basic principles of French laicité were not put into discussion.